The Development of the Self and Environmental Motivations Among Veiled Muslims in South Kalimantan, Indonesia - Faridah, Siti; Nirwana, Dzikri; Maimanah, M; Arni, A; Basrian, B; Hafidzi, Anwar (KnE Social Sciences, 2023)
Muslim women who cover their faces have gained popularity on Indonesian social media, which has prompted debate. Opinions have ranged from criticism of the veil’s exclusivity and religious exaggeration to associations between those who cover their faces and extremist Islamic activities. By communicating with veiled Muslim women in South Kalimantan, this paper aimed to shed light on these women and their relationship with wearing veils. The respondents were women in Banjarbaru, Banjarmasin, and Banjar Regency, aged between 30 and 50. They were interviewed, and the data went through descriptive-qualitative analysis. The methodology employed was qualitative with a religious psychology approach. The results showed that wearing the veil as an adult emphasised three factors: self-knowledge, self-assessment, and self-expectation, all of which are geared toward protecting oneself and gaining the same understanding as other Muslim women. Keywords: Self-Concept, Muslimah, Veiled, women